A luminescent covalent organic framework with recognition traps for nitro-pesticides detection, pH sensing and metal ions identification. (September 2022) - Fang, Xin; Liu, Yong; Han, Wang-Kang; Yan, Xiaodong; Shi, Ya-Xiang; Chen, Liang-Hui; Jiang, Yuqin; Zhang, Jiangwei; Gu, Zhi-Guo
Abstract: Special recognition sites in luminescent covalent organic frameworks (LCOFs) are extremely important to improve the selectivity of detection. Herein, we report on a novel LCOF named TFBD-Py-COF with three-in-one recognition traps composed of hydrogen bonding, reversible protonation of N and O–H⋯NC chelating unit. TFBD-Py-COF is synthesized via 3, 3′, 5, 5′-tetraformyl-4, 4′biphenyldiol (TFBD) and 4, 4′, 4″, 4‴-(pyrene-1, 3, 6, 8-tetrayl) tetra aniline (PyTTA), which has a two-dimensional dual rhombic pore structure based on AA stacking with the pore diameters of 0.88 and 1.38 nm. The hydroxyl group of TFBD-Py-COF can form hydrogen bonds with imines and induce the trans conformation of the mesoimine, as evidenced by the single crystal structure of the model compound. TFBD-Py-COF exhibits good chemical and thermal stability with a high BET surface area of 750 m 2 g −1 . TFBD-Py-COF shows visible fluorescent color from blue to green when dispersed in different organic solvents. TFBD-Py-COF has the fluorescence chemo-sensing ability for nitro-pesticides based on electron transfer-induced fluorescence quenching mechanism, allowing a high sensitivity and low detection limit of 4.0 × 10 −2 ppm for p -nitroaniline. In addition, TFBD-Py-COF shows reversible acidochromic behaviors and concomitant distinct fluorescent color change due to the protonation of the imine N. Furthermore, the fluorescence of TFBD-Py-COF is selectively quenched by Fe 3+ with a Ksv of 1.1 × 10 4 and a detection limit of 0.2 μM, owing to the coordination of Fe 3+ with the O–H⋯NC chelating unit. This study demonstrates great potential of LCOFs for multifunctional detection. Graphical abstract: Multi-target detection was realized by a luminescent COF which combines three-in-one recognition traps of hydrogen bonding, reversible protonation of N, and O-H…N=C chelating unit. Image 1 Highlights: A luminescent covalent organic framework (TFBD-Py-COF) was synthesized. TFBD-Py-COF has three-in-one recognition traps. TFBD-Py-COF exhibits excellent performance in nitro pesticide detection, pH sensing and metal ion identification.